Fatigue behaviors of square-to-square hollow section T-joint with corner crack I : experimental studies - Chiew, Sing Ping (2014)
Four full-size square-to-square hollow section (SSHS) T-joints were subjected to static and fatigue tests under combined loads. Static tests were first carried out to investigate the hot spot stress (HSS) distribution along the brace-chord intersections. Fatigue tests were then performed until extensive cracks appeared and the cracks development were monitored by the alternating current potential drop (ACPD) technique. The cracked joints were then opened up and the shapes of the crack surfaces were measured. Fatigue test results and crack geometry measurements showed that under cyclic loading, cracks will be initiated at one of the four corners of the brace-chord intersection and propagate mainly in the direction parallel to the chord wall. Furthermore, branches and secondary cracks, which seldom appear in circular hollow section (CHS) joints, were formed near the end of the test. The test results also indicated that a more stringent criterion should be used to define the fatigue life the joint. Finally, the shapes of the surface cracks of the tested joints were found to be more complicated than that for CHS joints and any of the existing geometrical model used in numerical modeling of CHS joint is deemed to be inadequate.